Problems of Legal Regulation of Election Campaign in the Republic of Armenia - Asatryan, Artak (Bulletin of Yerevan University C: Jurisprudence, 2022)
The election campaign plays a key role in the electoral process often predetermining the outcome of elections. The provisions on the election campaign of the Constitutional Law “Electoral Code of the Republic of Armenia” are discussed in the article. The problems and gaps in these provisions are highlighted and a number of proposals for their elimination are made. Special attention is paid to the latest amendments and additions to the chapter on Election Campaign of the Electoral Code, in particular, to the definitions of election campaign and political advertising, to the legal regulation of election campaign on the Internet, to the new restrictions for organizations to do charity during elections, to other limitations of election campaign, etc.
Keywords: Election campaign; elections; suffrage; electoral law; campaign poster; political advertising; election coverage; administrative proceedings; equal conditions for election campaign; campaign on the Internet; campaign in the media; campaign restrictions